Implementasi Game Based Learning Menggunakan Media Role Play untuk Meningkatkan Perkembangan Kognitif Siswa SMA Negeri 5 Palembang pada Mata Pelajaran Bahasa Inggris - Enjely Qurrotuaini; Rina Oktaviana (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This community service aims to enhance students’ cognitive development through Game Based Learning (GBL) using Role Play in English lessons at SMA Negeri 5 Palembang. The Role Play method allows students to assume roles according to predetermined scenarios to train their understanding, thinking skills, and cognitive development. The results of the community service indicate that the implementation of GBL with Role Play effectively improves student participation, speaking confidence, collaboration, and learning motivation. These interactive activities, supported by evaluations through quizzes and self-reflection, strengthen both academic and psychological awareness while comprehensively developing students’ cognitive and affective competencies.